2021
DOI: 10.1177/17448069211007289
|View full text |Cite
|
Sign up to set email alerts
|

Systemic gene expression profiles according to pain types in individuals with chronic spinal cord injury

Abstract: Pain affects most individuals with traumatic spinal cord injury (SCI). Major pain types after SCI are neuropathic or nociceptive, often experienced concurrently. Pain after SCI may be refractory to treatments and negatively affects quality of life. Previously, we analyzed whole blood gene expression in individuals with chronic SCI compared to able-bodied (AB) individuals. Most participants with SCI reported pain (N = 19/28). Here, we examined gene expression of participants with SCI by pain status. Compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Furthermore, TLRs are key receptors in various acute and chronic diseases, which can activate the inflammatory cascade and manifest by amplifying the inflammatory response (Iannotta et al, 2021). Reports have shown that SCI has a significant inducing effect on the TLR signalling pathway and induces pro‐inflammatory signals, such as NF‐κB, STAT signalling and lipopolysaccharide signalling (Morrison et al, 2021). Studies have shown that the TLR4 pathway is related to the induction of tactile allodynia, which is the main symptom associated with peripheral NP (T. Liu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TLRs are key receptors in various acute and chronic diseases, which can activate the inflammatory cascade and manifest by amplifying the inflammatory response (Iannotta et al, 2021). Reports have shown that SCI has a significant inducing effect on the TLR signalling pathway and induces pro‐inflammatory signals, such as NF‐κB, STAT signalling and lipopolysaccharide signalling (Morrison et al, 2021). Studies have shown that the TLR4 pathway is related to the induction of tactile allodynia, which is the main symptom associated with peripheral NP (T. Liu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The pain relief was profound, long-lasting, and with protracted onset, consistent with the drug having an impact on gene regulation. Derailed gene regulation underlies transition from acute to chronic pain (Okamoto et al, 2001;Wang et al, 2002;Hozumi et al, 2021;Morrison et al, 2021).…”
mentioning
confidence: 99%
“…Per established protocols [ 14 , 22 ], the paired sections were quickly washed, hydrated, and perforated using phosphate-buffered saline (PBS) with 0.03% Triton X-100 (PBST; Sigma-Aldrich) before blocking non-specific binding sites with 4% (vol/vol) normal donkey serum (Jackson ImmunoResearch Laboratories, West Grove, PA) in PBST for 1 h at room temperature. Different primary antibody solutions were added for incubations at 4 °C overnight, followed by quick PBST washing and reactions (1 h) with the corresponding secondary antibodies (Table 1 ) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…These data suggested that local and systemic inflammation may act as pathogenic factors to induce the evolvement of NP, pain-triggered complications, and other neural disorders p.i. (e.g., affective components of pain, distal motor neuron/neuromuscular junction abnormalities, and axon demyelination) [ 15 22 ]. However, to date, little has been done to systematically investigate NIF in the central nervous system (CNS) using clinically relevant SCI models.…”
Section: Introductionmentioning
confidence: 99%